2010
DOI: 10.1007/s10498-010-9112-1
|View full text |Cite
|
Sign up to set email alerts
|

Rate Equations and an Ion-pair Mechanism for Batch Dissolution of Gypsum: Repositioning the Shrinking Object Model at the Core of Hydrodynamic Modelling

Abstract: Recent improvements to experiments and modelling of batch dissolution in a turbulent reactor, based upon the shrinking object model, are extended to middle loadings of gypsum, that is, in the region between low and high loadings, which lead, respectively, to high under-saturation or saturation with a great excess of solid left undissolved. Dissolved calcium sulphate concentration was monitored by change in electrical conductivity. This investigation uses an improved, ion-pair model for CaSO 4 0 to allow for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
1
5
1
Order By: Relevance
“…This contrasts with earlier results (Truesdale 2011b) that did not completely follow the Solubility Product rule as in Fig. 1 (key empirical finding 3).…”
Section: The Role Of Gypsum Solubility C Sat In Parameterising Discontrasting
confidence: 99%
See 3 more Smart Citations
“…This contrasts with earlier results (Truesdale 2011b) that did not completely follow the Solubility Product rule as in Fig. 1 (key empirical finding 3).…”
Section: The Role Of Gypsum Solubility C Sat In Parameterising Discontrasting
confidence: 99%
“…The curves confirm that the same amount of gypsum (0.00582 M) dissolved in the two runs; these runs remained unsaturated. With the c sat values shown in Table 3, the linearised shrinking object model (Truesdale 2011b) fitted well to all of the plots, with the coefficient of determination (r 2 ) between 0.990 and 0.999 for 16-26 df (Table 3). There was a small, but nevertheless discernible, upwards curvature in the linearised data for the two runs at the highest initial calcium concentration, whence the intercepts for the fitted lines were forced about 3% below the origin.…”
Section: The Effect Of Ca 2? As Common Ion Upon the Dissolution Kinetmentioning
confidence: 88%
See 2 more Smart Citations
“…Such a release of sulfate from mushroom compost was also reported in a previous study (31.1 g kg À1 ; Guo et al, 2001). The potential source of sulfate in the mushroom compost could be either cow manure or gypsum (CaSO 4 2H 2 O), or both, since the former is a base material of mushroom compost and the dissolution of the latter can be enhanced through an ion-pair mechanism and the common ion effect (Truesdale, 2011). In a previous study, as much as 7 g kg À1 of sulfate was found to originate from a composted poultry manure substrate (Zagury et al, 2006).…”
Section: Sulfate Sulfide Doc and Srb Countssupporting
confidence: 82%